2020
DOI: 10.1017/s1360674320000325
|View full text |Cite
|
Sign up to set email alerts
|

foot-fronting andfootstrutsplitting: vowel variation in the East Midlands

Abstract: This article investigates the status of the foot–strut split in the counties of Leicestershire, Nottinghamshire and Derbyshire in the East Midlands of England. The East Midlands area is a linguistic transition zone between northern English varieties with a phoneme inventory of five short vowels, where foot and strut are represented by the same phoneme, and southern English varieties which have the foot–strut split and therefore six short vowels. However, a lack of research on the distribution of the foot and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…16 Crucially, in the same way as the SED, Leemann et al (2017Leemann et al ( , 2018 use the selection of the [ʌ]-like form as a proxy for presence of a distinction, which may result in an overestimation of the spread of the split. Indeed, recent results from Jansen and Braber (2021) in three East Midlands cities, which show that FOOT and STRUT are becoming more similar in their young East Midlands speakers, gives us added confidence in this interpretation of the state of the phonemic distinction today. In summary, these divergent interpretations on the presence of the FOOT-STRUT split in the Midlands highlight the problems with assuming phonemic status via survey methods that do not elicit structural properties, something originally highlighted by Wells (1978).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…16 Crucially, in the same way as the SED, Leemann et al (2017Leemann et al ( , 2018 use the selection of the [ʌ]-like form as a proxy for presence of a distinction, which may result in an overestimation of the spread of the split. Indeed, recent results from Jansen and Braber (2021) in three East Midlands cities, which show that FOOT and STRUT are becoming more similar in their young East Midlands speakers, gives us added confidence in this interpretation of the state of the phonemic distinction today. In summary, these divergent interpretations on the presence of the FOOT-STRUT split in the Midlands highlight the problems with assuming phonemic status via survey methods that do not elicit structural properties, something originally highlighted by Wells (1978).…”
Section: Discussionmentioning
confidence: 86%
“…While the nature of our data makes it impossible to investigate the exact phonetic realizations of STRUT, there are some advantages to the methodologies employed here: as discussed earlier in Section 1, the targeted questioning of our survey provides a more reliable indicator of the presence/absence of a phonemic split and the phonological status of this FOOT-STRUT contrast relative to other surveys such as the SED and the English Dialects App (Leemann, Britain & Blaxter, 2017;Leemann et al, 2018), which target only isolated phonemes and, in doing so, potentially overestimate the extent of the split, particularly in areas of the Midlands that are known to exhibit centralization of these vowels (see, for example, Jansen & Braber, 2021) and the aforementioned patterns of hypercorrection. That said, the isoglosses between the two present-day studies are very similar but with Leemann et al (2017) erring on the side of a distinction.…”
Section: Foot-strut Splitmentioning
confidence: 97%
“…A possible explanation for this sound change is the presence (or absence) of vowels in the same acoustic-perceptual space and an alleged tendency for vowels to avoid overlapping. Stockwell and Minkova (1997) as well as Fridland and Bartlett (2006), for example, argue that the fronting of back vowels is due to a relatively crowded back vowel space, which would create the conditions leading to goose -fronting and the fronting of foot and goat , respectively (e.g., Hall-Lew, 2009; Jansen & Braber, 2021; Watt & Tillotson, 2001). In the case of goose , the fronting might result in the vowel encroaching on the acoustic space of fleece (i.e., /i:/).…”
Section: Goose-fronting As a Sound Change In Varieties Of Englishmentioning
confidence: 99%
“…Braber (2016: 210) reinforces this notion stating that Nottingham is placed near isoglosses which tend to separate northern and southern varieties, including the FOOT/STRUT split. However, as discussed, Jansen and Braber (2020) found that for the FOOT/STRUT divide, there were differences across the East Midlands, but not in a way that patterns geographically from northern to southern varieties of English.…”
mentioning
confidence: 87%
“…In this sense, he regarded the Midlands as a whole as a transition zone from northern to southern English (ibid). Natalie Braber's research about East Midland English has explored this concept, and most recently Jansen and Braber (2020) researched the FOOT/STRUT split across the three counties that Braber tended to place in the East Midlands: Derbyshire, Nottinghamshire and Leicestershire, seeking to find evidence for its transition from northern to southern varieties across these counties. They did find differences in FOOT and STRUT, but not in a way that patterned geographically from northern to southern varieties of English.…”
Section: Bordersmentioning
confidence: 99%